Advancements in Telemedicine : Enhancing Patient Care in Remote and Underserved Areas - Aziz Haddou; Leila Benabdellah; Hassan Moudni (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
This paper explores the advancements in telemedicine and its potential to improve patient care, especially in remote and underserved regions. By examining the use of virtual consultations, mobile health apps, and remote monitoring tools, the research highlights how telemedicine facilitates access to healthcare, reduces costs, and increases patient satisfaction. The findings suggest that telemedicine is a vital tool in bridging healthcare gaps and improving healthcare delivery in rural areas.